(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the modern world, pedagogical activity acquires an active social status and purposefully implements the tasks of raising the educational level of leaders. The management process always takes place where the common activity of people is carried out to achieve certain results.